Finite element mesh generation - S.H. Lo , Daniel (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'Preface Nowadays, the finite element method has diverse applications to problems in science and engineering ranging from simple two-dimensional static elasticity, non-linear large deformation analysis to three-dimensional fluid dynamic problems with shock waves. The prerequisite for a finite element analysis is a sound and valid finite element mesh, which can only be constructed efficiently by means of some well-devised and thoroughly tested computer algorithms. In contrast to the numerous textbooks, monographs, journal papers, etc., on the finite element method, comprehensive and concise accounts on mesh generation technologies seem to have been missing, except perhaps the book Mesh Generation: Application to Finite Elements written by P.J. Frey and P.L. George some 15 years ago. Anyway, finite element mesh generation has not been taken as a formal subject of teaching in universities, as it encompasses several disciplines including classical geometry, computational geometry and topology, finite element method, data structures and algorithms, computer programming and, to a certain extent, even computer graphics. With the ever-improving performance of PCs, large-scale challenging engineering simulations and scientific computations by means of the finite element method are more accessible to daily design operations and even to research students. In line with this development, the mesh generation methodology is becoming increasingly recognised as a subject in its own right. As meshing technologies and their applications in new areas have developed pretty rapidly over the recent years, it is imperative to review and consolidate the progress in meshing technologies achieved thus far into a concise yet comprehensive text with a logical'--
'A Spon book.'
Includes bibliographical references : pages 569-598 and index.
Keywords: Numerical grid generation (Numerical analysis).; Finite element method